An afrocentric exploration of the socio-cultural challenges confronted by Africa students in historically disadvantaged universities in South Africa: the case of University of the North, 1970-1994 - Lekgau, Phakiso (My University, 2022)
This study explores the socio-cultural experiences of students at the University of the North (UNIN) in the period between 1970 and 1994. The sampling of the study was purposive and involved thirteen (13) participants who were students at UNIN in the 1970s, 80s and 1990-1994. Data was collected using an interview guide and was analysed using the Thematic Content Analysis as outlined by Braun and Clark (2011). To make sense of the study aim and objectives, this study adopted a qualitative approach wearing an Afrocentric pair of lenses. As shown by literature and the study’s findings, Historically Black Universities (HBUs) in South Africa were established by the apartheid government with the aim of serving Black students excluded from attending segregated White-only universities. Some of the study findings are that former UNIN students were subjected to a racialised institutional autonomy, racialised educational curriculum as well as an unfriendly academic setting for both African students and staff. The study therefore argues for inclusive and Africanised institutions of higher learning in Africa and perhaps elsewhere in the world. This study also recommends that institutional autonomy and educational curricula should be in line with an Africanised value system.
Thesis (M.A. (History)) -- University of Limpopo, 2022
Keywords: Educational curricula; University of the North; Apartheid; socio-cultural; Social change; Education -- Curricula; Education, Higher -- South Africa -- Limpopo; African students